Impact of dust size parameterizations on aerosol burden and radiative forcing in RegCM4 - A. Tsikerdekis (Atmospheric Chemistry and Physics, 2017)
We investigate the sensitivity of aerosol representation in the regional climate model RegCM4 for two dust parameterizations for the period 2007–2014 over the Sahara and the Mediterranean. We apply two discretization methods of the dust size distribution keeping the total mass constant: (1) the default RegCM4 4-bin approach, where the size range of each bin is calculated using an equal, logarithmic separation of the total size range of dust, using the diameter of dust particles, and (2) a newly implemented 12-bin approach with each bin defined according to an isogradient method where the size ranges are dependent on the dry deposition velocity of dust particles. Increasing the number of transported dust size bins theoretically improves the representation of the physical properties of dust particles within the same size bin. Thus, more size bins improve the simulation of atmospheric processes. The radiative effects of dust over the area are discussed and evaluated with the CALIPSO dust optical depth (DOD). This study is among the first studies evaluating the vertical profile of simulated dust with a pure dust product. Reanalysis winds from ERA-Interim and the total precipitation flux from the Climate Research Unit (CRU) observational gridded database are used to evaluate and explain the discrepancies between model and observations. The new dust binning approach increases the dust column burden by 4 and 3 % for fine and coarse particles, respectively, which increases DOD by 10 % over the desert and the Mediterranean. Consequently, negative shortwave radiative forcing (RF) is enhanced by more than 10 % at the top of the atmosphere and by 1 to 5 % on the surface. Positive longwave RF locally increases by more than 0.1 W m−2 in a large portion of the Sahara, the northern part of the Arabian Peninsula and the Middle East. The four-bin isolog method is to some extent numerically efficient, nevertheless our work highlights that the simplified representation of the four-bin approach produces less dust optical depth and RF, a fact that should be taken into account by future studies of the same region.